Quiet Quitting in Public Institutions: A Descriptive Content Analysis - Esen, Dilek (International Journal of Contemporary Economics and Administrative Sciences, 2023)
The study discussed quiet quitting (QQ) in the public sector context. In this context, it has been investigated the definition of quiet quitting in the public sector, individual and organizational factors contributing to QQ, the importance of managers in Quiet Quitting (QQ), the consequences of Quiet Quitting Behavior (QQB), and the effects of the pandemic. The data were obtained through in-depth interviews conducted with 13 voluntary participants working in public institutions. Maxqda Program was used for analyzing the data. According to the results, it was concluded that QQB could be more prevalent among individuals with longer tenure and older age in public institutions. In public institutions, QQ was expressed through the concepts of "System Problem and Desperation," "Attitude," "To be offended," and "Passive aggression-Emotional Dissatisfaction". The most intense emotions felt by those experiencing the QQ process were devaluation, unhappiness, and desperation. The primary organizational reasons for QQB were found to be a lack of motivation and recognition.